2021
DOI: 10.14218/jcth.2021.00046
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Hepatitis B Infection with Low Level Viremia Correlates with the Progression of the Liver Disease

Abstract: Background and Aims Currently, insufficient clinical data are available to address whether low-level viremia (LLV) observed during antiviral treatment will adversely affect the clinical outcome or whether treatment strategies should be altered if LLV occurs. This study compared the clinical outcomes of patients with a maintained virological response (MVR) and patients who experienced LLV and their treatment strategies. Methods A retrospective cohort of 674 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…We found that patients who changed their treatment were more likely to achieve complete virological suppression than those who continued the original treatment and that their long-term clinical outcomes were better. At the same time, we found no significant difference in the CVR between switching to another drug and adding on a drug [31] ; however, due to our limited data, these conclusions may be biased and require further validation in a larger population. In a recent study in which patients with LLV were treated with ETV or NUC combination therapy, almost all patients achieved complete virological suppression when switching to TAF treatment after 48 weeks; at the same time, patients with CKD converted to TAF, and their eGFR also improved (+ 0.40 mL · min −1 · 1.73m −2 ), suggesting that patients with LLV need more effective treatment and that TAF is a safe and effective choice [30] .…”
Section: Management Of Llvcontrasting
confidence: 54%
“…We found that patients who changed their treatment were more likely to achieve complete virological suppression than those who continued the original treatment and that their long-term clinical outcomes were better. At the same time, we found no significant difference in the CVR between switching to another drug and adding on a drug [31] ; however, due to our limited data, these conclusions may be biased and require further validation in a larger population. In a recent study in which patients with LLV were treated with ETV or NUC combination therapy, almost all patients achieved complete virological suppression when switching to TAF treatment after 48 weeks; at the same time, patients with CKD converted to TAF, and their eGFR also improved (+ 0.40 mL · min −1 · 1.73m −2 ), suggesting that patients with LLV need more effective treatment and that TAF is a safe and effective choice [30] .…”
Section: Management Of Llvcontrasting
confidence: 54%
“…A low level of viremia is an independent risk factor for HCC, especially the patients with hepatocirrhosis accompanying low viremia, the risk of HCC increases when the clinicians should consider adjusting the therapeutic regime. [ 34 ] Otherwise, the occurrence of HCC is also possible in the immune tolerance, so looking for a proper beginning, and end of antiviral treatment and launching antiviral treatment in the early stage will be a better strategy, which can reduce the risk of HCC in patients in the gray zone; however, more clinical research evidence is needed to reach this goal. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that NA treatment could effectively suppress HBV viral replication in patients with CHB despite ALT levels < 2 × ULN. Importantly, the existence of serum HBV DNA levels is a strong predictor of risk for HCC [ 18 , 19 ], and the decline of DNA levels could reduce the incidence of HCC risk [ 20 ]. It can be shown that decreasing viral loads can benefit patients by reducing the occurrence of adverse events.…”
Section: Discussionmentioning
confidence: 99%